Fauna of Culex Mosquitoes In Salamwates Village Dongko Subdistrict, Trenggalek City - Mardliyana Shalihah; Budi Utomo; Subagyo Yotopranoto; Heny Arwati (Biomolecular and Health Science Journal, 2020)
Introduction: Mosquito-borne diseases are still a burden worldwide, including in Indonesia. Some of those diseases, such as filariasis and Japanese encephalitis, are transmitted by some species of Culex mosquitoes. We aimed to describe the fauna of Culex mosquitoes in Salamwates village, Dongko subdistrict, Trenggalek district. Methods: Female Culex mosquitoes were collected in Salamwates village at night using the methods of indoor human-baited double bed-net trap and outdoor cow-baited double bed-net trap. The spesies of collected Culex mosquitoes were identified based on identification guide published by Ministry of Health of Republic Indonesia. Results: There were 67 identifiable female mosquitoes collected using cow-baited methods and no female mosquitoes collected using human-baited methods. Those mosquitoes consisted of nine species. Culex tritaeniorhynchus (29.85%), C. gelidus (23.88%), C. vishnui (13.43%), C. pseudovishnui (11.94%) were the dominant species. The peaks of biting activities were at 18.45-19.00 and 23.45-24.00.  Conclusion: Nine species of Culex mosquitoes collected using cow-baited methods. C. tritaeniorhynchus was the dominant species. Those mosquitoes were zoophilic and exophagic. The peaks of biting activities of the Culex mosquitoes were at dusk and midnight.